2014
DOI: 10.1007/s00345-014-1376-4
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability of R.E.N.A.L., PADUA, and centrality index nephrometry score systems

Abstract: Purpose To assess interobserver variability of R.E.N.A.L., PADUA, and C-Index systems among observers with varying degrees of clinical experience and each system's subscale correlation with surgical outcome metrics. Methods Computed tomography images of 90 patients who underwent open, laparoscopic, or robot-assisted laparoscopic partial nephrectomy were scored by 1 radiology fellow, 2 urology fellows, 1 radiology resident, and 1 secondary school student. Agreement among readers was determined calculating int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 15 publications
1
46
0
2
Order By: Relevance
“…The RENAL and PADUA scoring systems were built on the morphologic attributes of renal tumors primarily to facilitate communication of tumor anatomy [1,2]. However, cutoff values for some of these systems’ components, for example, maximal tumor size or nearness to the renal sinus structures were chosen based on simplicity rather than proven clinical relevance in predicting surgical outcomes [1,13]. In a recent critical evaluation of the RENAL and PADUA scoring systems and centrality index, only four predictors of complexity (radius, nearness to the collecting system, location relative to the lateral rim, and centrality) were found to be clinically significant variables on multivariable analysis [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The RENAL and PADUA scoring systems were built on the morphologic attributes of renal tumors primarily to facilitate communication of tumor anatomy [1,2]. However, cutoff values for some of these systems’ components, for example, maximal tumor size or nearness to the renal sinus structures were chosen based on simplicity rather than proven clinical relevance in predicting surgical outcomes [1,13]. In a recent critical evaluation of the RENAL and PADUA scoring systems and centrality index, only four predictors of complexity (radius, nearness to the collecting system, location relative to the lateral rim, and centrality) were found to be clinically significant variables on multivariable analysis [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we found that increasing radiological and clinical experience reduced the interobserver variability of these systems and that only subscales measuring tumor size and distance to intrarenal structures had clinical significance [13]. Other contemporary studies confirmed that reproducibility of nephrometry scores is affected by the level of the reader’s training and experience [14,15].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, they were not devoid of limitations. A recent study indicated that the inter‐observer variability of these systems can be reduced by enhanced radiological and clinical experience . Other studies verified that the level of the observer's training and experience has an influence on reproducibility of nephrometry scores .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, each nephrometry score's ability to predict clinically relevant outcomes of PN ranges from study to study . Lastly, nephrometry score constituents such as descriptor of posterior or anterior and location relative to polar lines used for RENAL nephrometry score; posterior or anterior face, polar location, and margin location of the tumor, and exophytic rate in the PADUA scoring system, seem to perform poor in predicting clinically relevant outcomes of PN …”
Section: Discussionmentioning
confidence: 99%